Genetic diversity assessment in Pinus laricio Poiret populations using microsatellites analysis and inferences on population hystory - Bonavita; Musacchio, Aldo; Regina, Teresa M. R.; Bernardini, Vincenzo (My University, 2012)
Forests are complex and dynamic ecosystems characterized by trees with remarkable longevity and reproductive forms, particularly, cross-pollination which tend to increase their degree of genetic diversity. If on the one hand, cross-pollination between different individuals continuously shuffles the genetic material ensuring heterogeneity, on the other hand, an effective pollen and seeds dispersal ensures a reliable gene flow between individuals and, therefore, high levels of intra-specific variability. Therefore, more genetically different individuals are, greater is their ability to adapt to changed environmental conditions. Pinus laricio Poiret, usually considered as the most divergent and genetically original subspecies of European black pine (Pinus nigra Arnold), is the most widespread conifer occurring in Calabria, Sicily (Etna Mount) and Corsica. In Calabria, it grows on the Aspromonte mountain and mainly on the Sila plateau, where laricio pine forests cover more than 40,000 ha and characterize the landscape from 900 m up to 1,700 m above sea level. Thermophilic, xerophilous and heliophilous species, Pinus laricio can reach large sizes and 350 years of age, as documented for the Fallistro's Giants Biogenetical Reserve, within the Sila National Park. To the best of our knowledge, until now no studies have been conducted on the genetic diversity of Pinus laricio forests in their natural range of distribution. Furthermore, an in-depth investigation on the within- and among-population genetic differentiation is greatly needed to preserve Pinus laricio diversity, but also to establishing appropriate strategy of management and conservation of this specie. In this thesis, genetic polymorphism among geographically distant laricio pine natural populations from Sila, Aspromonte, Etna, and Corsica National Parks was detected using chloroplast and nuclear SSR markers. Both types of markers revealed that the higher diversity was found mainly within populations, while there were low levels of differentiation among populations, very likely associated with extensive gene flow and strong anthropogenic influence. However, a geographical discontinuity was identified, clearly indicating genetic subdivision of the investigated laricio pine populations at both inter- and intra-population level. All populations within the Sila area were found differentiated from the rest, particularly the Fallistro population that appeared the most genetically distinct. Results issued from this study shed light on the gene pool and evolutionary history of Pinus laricio populations providing a genetic perspective for exploitation and conservation of this not yet sufficiently explored resources in forestry.
Dottorato di Ricerca in Biologia animle, Scuola di Dottorato “Life Sciences”, Ciclo XXV, a.a. 2011-2012
Keywords: Biologia vegetale; Pini; Pinus laricio